2010
DOI: 10.1111/j.1743-6109.2009.01557.x
|View full text |Cite
|
Sign up to set email alerts
|

More than Sexual Function: Predictors of Sexual Satisfaction in a Sample of Women Age 40–70

Abstract: Introduction The literature provides a complex picture of sexual satisfaction and its predictors. To date, studies have provided a list of predictors of sexual satisfaction, including relational and psychological factors, but very little information is available on the direct effects of these predictors in midlife women, independently from the effects of sexual function on sexual satisfaction. Aim The main aim of this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 52 publications
5
86
1
9
Order By: Relevance
“…In the Wisconsin Longitudinal Study (DeLamater et al, 2008), satisfaction with one's relationship or marriage was the strongest predictor of participants' satisfaction with their sexual relationship. Similarly, in a clinical sample of 86 women aged 40-70 years, relationship-related indicators were stronger predictors of sexual satisfaction than sexual function (Dundon & Rellini, 2010). The importance of relationship quality was indirectly corroborated in a crosscultural study that found physical intimacy a significant correlate of sexual satisfaction regardless of gender (Heiman et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 53%
See 4 more Smart Citations
“…In the Wisconsin Longitudinal Study (DeLamater et al, 2008), satisfaction with one's relationship or marriage was the strongest predictor of participants' satisfaction with their sexual relationship. Similarly, in a clinical sample of 86 women aged 40-70 years, relationship-related indicators were stronger predictors of sexual satisfaction than sexual function (Dundon & Rellini, 2010). The importance of relationship quality was indirectly corroborated in a crosscultural study that found physical intimacy a significant correlate of sexual satisfaction regardless of gender (Heiman et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 53%
“…Chronic illnesses such as diabetes, cardiovascular problems, arthritis and fatigue have been implicated as the core of physical health problems affecting sexual satisfaction (DeLamater et al, 2008;Field et al, 2013;Syme et al, 2013). Similar empirical support has been obtained for the importance of mental health problems, particularly those related to depression and anti-depressant medication use (Dundon & Rellini, 2010;Kim & Jeon, 2013;McCall-Hosenfeld et al, 2008;Scott et al, 2012;Thompson et al, 2011;Wang et al, 2014). Finally, moderate to strong associations between sexual satisfaction and well-being, and sexual health disorders or impaired sexual function (Ratner, Erekson, Minkin, & Foran-Tuller, 2011) have been consistently observed (Heiman et al, 2011;Laumann et al, 2006;Traeen & Schaller, 2010).…”
Section: Predictors and Correlates Of Sexual Satisfaction In Older Agementioning
confidence: 60%
See 3 more Smart Citations